Healthful school environment as determinant of junior secondary school students’ hygiene behaviour in Afijio Local Government Area of Oyo State, Nigeria (2015)
The study investigated healthful school environment as determinant of Junior Secondary School students' hygiene behaviour. The descriptive survey research design was employed in the study. A sample of 487 respondents were selected using simple random sampling technique. The instrument used was self developed questionnaire with reliability co-efficient of 0.61. The data was analysed with the use of percentage and inferential statistics of multiple regression at 0.05 level of significance. The result showed that, joint effect of variables of healthful school environment of (safe drinking water, hand and body washing equipment and facilities, toilet facilities, sanitary equipment and environmental aesthetic) on students ‘ hygiene behaviour was significant; F(5,481)=65.915;R= 638; R2 =.407. Adj. R2 = .400; P<05. The paper concluded that, positive hygiene behaviour was a step towards achieving good health and could be fostered in students by the provision of healthful school environment. It was recommended that, government at all levels should make human and material resources available in schools to facilitate the implementation of healthful school environmental programme.